Vildagliptin With Metformin Once-Daily Regimen-Insights From a Single-Center Analysis. (May 2015) - Chatterjee, Sanjay; Chatterjee, Saurav
Abstract : Dipeptidyl peptidase-4 (DPP-4) inhibitors have been well established as an adjunctive treatment to metformin. Most guidelines recommend treatment with a DPP-4 inhibitor, vildagliptin, in addition to metformin in a twice-daily regimen. However, the twice-daily regimen has difficulty with medication adherence, increased cost of therapy, and possibility of more side effects. Our objective was to evaluate, by means of retrospective analysis, the efficacy of once-daily metformin and vildagliptin (a DPP-4 inhibitor) in reducing blood glucose for patients on combination therapy. We analyzed data from our database of outpatients attending the diabetic clinic at a tertiary care center in Kolkata, India. We had data on once-daily combination of metformin and vildagliptin for 154 patients between September 2008 and May 2012. We followed up these patients for a median of 17.6 months and evaluated posttherapy glucose levels and hemoglobin A1c. Continuous variables were compared with t tests. Once-daily metformin–vildagliptin combination was found to be associated with a mean reduction of 27.52 mg/dL of fasting plasma glucose, 71.70 mg/dL of postprandial plasma glucose, and 1.41% reduction of HbA1c ( P < 0.05 for all). Metformin–vildagliptin combination in a once-daily regimen seems to be associated with significant reductions in plasma glucose and HbA1c and may be a viable and cost-effective alternative to a twice-daily regimen as starting therapy.